Socio-economic determinants of intimate-partner physical violence among women in South Africa - Mabena, Keatlegile; Tsabedze, Wandile; Mazibuko, Xolisa (Frontiers in Psychology, 2025)
IntroductionIntimate partner violence (IPV) against women is a worldwide public health and human rights problem that occurs in various forms which includes physical, emotional, and sexual abuse. It is commonly perpetrated by the male intimate partner. This phenomenon cuts across the global South regions, including South Africa. In South Africa, women bear the brunt of intimate-partner physical violence, there is a need to reduce femicide and highlight the preponderance of intimate-partner physical violence in South Africa.MethodsThe main objective is to explore the socio-economic determinants of IPV among women in South Africa. Data are drawn from the 2016 South Africa Demographic and Health Survey 2016. The total sample (8,514) of women aged 15–49 years was selected and interviewed for domestic violence. The sampling method used for the survey conducted was a stratified sample selected in two stages, with enumeration areas (EA) as the sampling units for the first stage. Univariate analysis was performed to show the distribution of the variables in the study followed by bivariate analysis (Pearson's chi-square statistics) showing the relationship between individual variables and the dependent variable.ResultsUsing multivariate analysis (Binary regression model) to determine the socio-economic variables revealed the significance of p < 0.01–p < 0.04, p < 0.005–p < 0.009 and p < 0.005, associated with the dependent variable while controlling for the effects of other variables. The results revealed significant Odds Ratios (ORs) that highest educational attainment, ORs (1.565), wealth index, ORs (poorer = 0.883, middle = 0.924), employment status ORs (1.073), current marital status, ORs (married = 0.425, living together = 0.479, divorced/separated = 0.422), and justifying wife-beating ORs (yes = 3.030).ConclusionThis shows the need for policymakers to address physical violence by placing an emphasis on formulation of programmes and policies that empower women through education, employment, and political participation.